2003
DOI: 10.1002/eqe.302
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic earthquake response of single‐story asymmetric buildings: an assessment of simplified shear‐beam models

Abstract: SUMMARYThe inelastic seismic torsional response of simple structures is examined by means of shear-beam type models as well as with plastic hinge idealization of one-story buildings. Using mean values of ductility factors, obtained for groups of ten earthquake motions, as the basic index of post-elastic response, the following topics are examined with the shear-beam type model: mass eccentric versus sti ness eccentric systems, e ects of di erent types of motions and e ects of double eccentricities. Subsequentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…For asymmetric frame buildings like those designed for this study following the EC8 dynamic procedure, the critical elements are the frames at the flexible edges of the building. This is predicted both by the detailed, realistic, MDOF, models, as well as by the simplified models having the correct element strengths (SIMP1 and SIMP2) and confirms similar findings for one-story buildings reported in [26]. 2.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…For asymmetric frame buildings like those designed for this study following the EC8 dynamic procedure, the critical elements are the frames at the flexible edges of the building. This is predicted both by the detailed, realistic, MDOF, models, as well as by the simplified models having the correct element strengths (SIMP1 and SIMP2) and confirms similar findings for one-story buildings reported in [26]. 2.…”
Section: Discussionsupporting
confidence: 89%
“…Subject to the limitations imposed by the underlying assumptions, the results in this paper confirm earlier findings pointing to inadequacies of the simplified, one-story, shear-beam-type systems, 538 S. A. ANAGNOSTOPOULOS, C. ALEXOPOULOU AND K. G. STATHOPOULOS for predicting the inelastic response of real, asymmetric, multistory frame buildings, subjected to torsion due to earthquake motions and consequently for deriving general conclusions about torsional provisions of the codes [25,26,28,31]. Using as the basis for comparison, the predictions of such response by detailed, multistory models of the PH type, it was found that:…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…By adopting a 3D plastic hinge model, which closely approximates actual frame structures, Stathopoulos et al [20] conducted inelastic dynamic time history analysis of multistorey bidirectional eccentric structures. In contrast to related noneccentric systems, the so-called flexible side frames had more ductility requirements than that of stiff side frames; this finding was also different from previous results using the simplified one-storey model [21]. Rizwan et al [22] utilized the SAP2000 to construct a plastic hinge model of a 3D frame structure and conducted nonlinear dynamic history analysis on two kinds of asymmetric structures.…”
Section: Introductioncontrasting
confidence: 51%